UPAYA PENINGKATAN SIKAP DAN AKHLAK DALAM MATA PELAJARAN AGAMA ISLAM DI SEKOLAH MTS, MUHAMMADIYAH BONTORITA - Abdul Aziz, Ilmas Uzza; Pasaribu, Munawair (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2023)
Islamic Religious Education (PAI) is one of the subjects that has a high influence in shaping the personality character of students in schools. Teachers who teach these lessons usually have an important role in deciding religious matters in schools. Moral education can also be interpreted as a formulation of the moral education process that is carried out broadly and holistically. . Moral education materials can synergize with all subjects, school culture, extracurricular activities, and with the community. It is said that the integrative scientific structure does not mean that the various sciences are merged into one identical form of science, but rather that the character, pattern, and nature of the science are integrated in the unity of the spiritual material dimension, reason-revelation, general science-religious science, physical-spiritual, and the afterlife. Integration requires a relationship or unification or synchronization or interplay or alignment between each existing scientific field. Each scientific field cannot stand alone, without greeting each other with other scientific fields. Meanwhile, inclusive education is something related to many aspects of human life which are based on the principles of equality, justice, and individual rights. So integrative-inclusive education means that an educational process should cover a wide and thorough scope. Integrative-inclusive moral education has a comprehensive and holistic scope.